Solid electrolyte material, preparation method and all-solid-state lithium-ion battery
The solid electrolyte material with the chemical formula (Li5-xMx/a)Y (A3-yXy/b) was prepared by high-temperature and high-pressure sintering, which solved the problem of insufficient conductivity and stability of solid electrolyte materials in the prior art, and achieved the preparation of high-purity and low-cost all-solid lithium-ion battery electrolyte materials.
Patent Information
- Application Number
- CN202210656159.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-10
- Publication Date
- 2025-08-15
- Estimated Expiration
- 2042-06-10
AI Technical Summary
The existing solid electrolyte materials have low ionic conductivity and electrochemical stability, and it is difficult to synthesize high-purity solid electrolytes in traditional preparation methods.
The solid electrolyte material with the chemical formula (Li5-xMx/a)Y(A3-yXy/b) is synthesized with a hexagonal crystal structure by sintering under conditions of 300°C and above, 0.2 GPa and above through high-temperature and high-pressure technology, and the moisture content is limited to less than 0.01 ppm.
The ionic conductivity and electrical properties of all-solid-state lithium-ion batteries are improved, the preparation cost is reduced, and a high-purity solid electrolyte material is obtained.
Smart Images

Figure CN115000500B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and more specifically, to a solid electrolyte material, a preparation method, and an all-solid-state lithium-ion battery. Background Art
[0002] Metal ion batteries have incomparable advantages such as high energy density, high output voltage, long service life and environmental friendliness, making them irreplaceable and excellent energy storage devices.
[0003] Currently, commercial metal-ion batteries generally use organic liquid and gel electrolytes, which inevitably introduce volatile, flammable, explosive, and toxic organic liquids into the battery system, posing serious safety risks. In contrast, solid-state electrolytes offer significant advantages in safety, thermal stability, and electrochemical stability. Therefore, vigorously developing all-solid-state metal-ion batteries is essential to fundamentally addressing battery safety issues. Developing high-performance solid-state electrolyte materials is a crucial step in the development of all-solid-state batteries.
[0004] At present, the solid electrolytes that have been reported include NASICON-type electrolytes, LISICON-type electrolytes, perovskite-type solid electrolytes, antiperovskite-type solid electrolytes, garnet-type electrolytes and sulfide electrolytes.
[0005] However, the ionic conductivity and electrochemical stability of existing solid electrolytes need to be further improved. In addition, most researchers use traditional methods such as high-temperature solid-phase method, sealed tube method, and melting method to prepare solid electrolytes, which makes it difficult to synthesize pure phase solid electrolytes. Summary of the Invention
[0006] Based on the above-mentioned deficiencies, the present application provides a solid electrolyte material, a preparation method and an all-solid-state lithium-ion battery to partially or completely improve or even solve the problem in the related art that it is difficult to synthesize a pure phase, high conductivity and good stability solid electrolyte material.
[0007] The above technical problems of this application are achieved through the following technical solutions:
[0008] In a first aspect, the example of the present application provides a solid electrolyte material, the chemical formula of the solid electrolyte material is (Li 5-x M x / a )Y(A 3-y X y / b), the solid electrolyte material belongs to the hexagonal system; wherein M is a cation with a valence of a, and Y, A, and X are all anions. M includes one or more of H, Na, K, Rb, Mg, Ca, Sr, Ba, Zn, Al, Ga, Si, Ge, Sn, and P; Y is selected from at least one of O, S, and Se; A is selected from one of F, Cl, Br, and I; X has a valence of -b and is selected from at least one of F, Cl, Br, I, S, O, Se, N, OH, BF4, BH4, AlF4, and AlH4 that is different from A; 0≤x<5, 0≤y≤3.
[0009] In the above implementation process, the example of the present application provides a new chemical formula (Li 5-x M x / a )Y(A 3- y X y / b ) solid electrolyte material, which is a hexagonal crystal system and has high ionic conductivity. The use of this solid electrolyte material to prepare an all-solid-state metal ion battery can improve the electrical properties of the corresponding all-solid-state metal ion battery, such as ionic conductivity, charge and discharge cycle performance, etc. (For example, in order to adapt to all-solid-state lithium-ion batteries, the solid electrolyte material with the chemical formula of Li5YA3 provided in this application can be selected; in order to adapt to all-solid-state sodium-ion batteries, the solid electrolyte material with the chemical formula of (Na 4.9 Li 0.1 )YA3 solid electrolyte material).
[0010] In combination with the first aspect, in a first possible implementation manner of the first aspect of the present application, the chemical formula of the solid electrolyte material is Li5YA3;
[0011] Optionally, the chemical formula of the solid electrolyte material is Li5OA3;
[0012] Optionally, the chemical formula of the solid electrolyte material is Li5OBr3;
[0013] Optionally, the solid electrolyte material has the chemical formula Li 5-x Mg x / 2 OA3, where 0 <x<5;
[0014] Optionally, the solid electrolyte material has the chemical formula Li5SBr 3-y Cl y , where 0≤y≤3;
[0015] Optionally, the solid electrolyte material has the chemical formula Li5OBr 3-y S y / 2 , where 0 <y≤3。
[0016] All-solid-state lithium-ion batteries have incomparable advantages such as high energy density, high output voltage, long service life, and environmental friendliness, and are an excellent energy storage device. In the above implementation process, this application example provides a chemical formula of Li5Y(A 3-y X y / b ) can be used in a solid electrolyte material for all-solid-state lithium batteries. The solid electrolyte material has high ionic conductivity and can improve the electrical performance of all-solid-state lithium-ion batteries.
[0017] In a second aspect, an example of the present application provides a method for preparing a solid electrolyte material, the preparation method comprising:
[0018] A sintered body is obtained, wherein the sintered body comprises 5-x M x / a )Y(A 3-y X y / b ) in a stoichiometric ratio; the water content of the sintered body is less than 0.01 ppm;
[0019] The sintered body is placed under a preset temperature, a preset pressure and a moisture content of less than 0.01 ppm for a preset time;
[0020] Among them, the preset temperature is not lower than 300°C, the preset pressure is not less than 0.2GPa, and the preset time is not less than 5 minutes.
[0021] In the above implementation process, the example of the present application provides a method for preparing a solid electrolyte material containing a solid electrolyte material according to the chemical formula (Li 5-x M x / a )Y(A 3-y X y / b ) is placed in the sintered body of raw materials prepared in a stoichiometric ratio at a temperature of 300°C or above, a pressure of 0.2GPa or above, and a moisture content of less than 0.01ppm for at least 5 minutes. The high temperature and high pressure technology can be used to make the raw materials in the sintered body chemically react to form a composite material with the chemical formula (Li 5-x M x / a )Y(A 3-y X y / b ) and a new solid electrolyte material with a hexagonal crystal structure.
[0022] At the same time, by limiting the moisture content of the green body to be sintered and the moisture content of the green body to be sintered during the high-temperature and high-pressure reaction sintering process, it is avoided that the raw materials are in contact with moisture and thus affect the synthesis reaction of the solid electrolyte material.
[0023] The above preparation method is simple to operate, can shorten the preparation time, and obtain a solid electrolyte material with higher purity.
[0024] In combination with the second aspect, in a first possible implementation manner of the second aspect of the present application, the body to be sintered includes Li2Y, LiA, and LiX in a stoichiometric ratio of 1:(3-y):y;
[0025] Optionally, the body to be sintered comprises Li2O, LiA and LiX in a stoichiometric ratio of 1:(3-y):y;
[0026] Further optionally, the body to be sintered comprises Li2O, LiBr and LiCl in a stoichiometric ratio of 1:(3-y):y;
[0027] Further optionally, the body to be sintered includes Li2O and LiBr in a stoichiometric ratio of 1:3.
[0028] In the above implementation process, the green body to be sintered includes Li2O, LiA and LiX weighed according to the stoichiometric ratio of 1: (3-y): y, so that the green body to be sintered is subsequently subjected to a high temperature and high pressure reaction to synthesize a high purity chemical formula (Li 5-x M x / a )Y(A 3-y X y / b ) solid electrolyte material to improve the electrical performance of all-solid-state lithium-ion batteries. Moreover, the lithium-containing solid electrolyte material suitable for all-solid-state lithium batteries prepared by this method can improve the electrical performance of all-solid-state lithium-ion batteries while reducing the preparation cost of all-solid-state lithium batteries (compared with solid electrolytes with the same electrical performance obtained by traditional preparation methods, the preparation method of the lithium-containing solid electrolyte material provided by this application is simple to operate, has a short preparation time, and has a high product purity, thereby reducing the preparation cost of all-solid-state lithium batteries).
[0029] In conjunction with the second aspect, in a second possible implementation manner of the second aspect of the present application, a method for preparing the body to be sintered includes:
[0030] Step 1: Under the condition that the water content is less than 0.01ppm, the raw materials are prepared according to the chemical formula (Li 5-x M x / a )Y(A 3-y X y / b ) in a stoichiometric ratio to prepare a first mixed material;
[0031] Step 2: Press the first mixture under a pressure of 20-100 MPa for 1-5 minutes under the condition that the moisture content is less than 0.01 ppm.
[0032] In the above implementation process, under the condition that the moisture content is less than 0.01ppm, the chemical formula is (Li 5-x M x / a )Y(A 3-y X y / b) is mixed with the raw materials weighed in a stoichiometric ratio, which can prevent the various raw materials from absorbing moisture and affecting the reaction synthesis of the solid electrolyte material, so that the raw materials are evenly dispersed, which is convenient for improving the purity of the solid electrolyte material synthesized by subsequent high-temperature and high-pressure technology reactions (if not evenly dispersed, the components in the prepared product are unevenly dispersed, and it is difficult for the corresponding elements to undergo diffusion reactions to obtain the chemical formula (Li 5-x M x / a )Y(A 3-y X y / b ) of a new solid electrolyte material of the hexagonal system, thereby reducing the purity of the obtained solid electrolyte material).
[0033] Furthermore, under the condition that the moisture content is less than 0.01ppm, the mixed first mixture is pressed under a pressure of 20-100MPa for 1-5min to obtain a pre-pressed green body with a specific shape. By pre-pressing, the various raw material powders mixed evenly can be kept relatively uniform during the sintering process, the holes are reduced, a certain pressure exists between the raw material powders, the contact between the particles is closer, the migration distance of the particles is shorter, and the chemical formula (Li 5-x M x / a )Y(A 3-y X y / b ) to synthesize a new type of hexagonal solid electrolyte material and improve the synthesis efficiency.
[0034] In addition, pressing the first mixture at a pressure of 20-100 MPa for 1 to 5 minutes can give the to-be-sintered green body a specific shape and a certain density, making it easier for operators to perform high-temperature and high-pressure reaction synthesis operations on the to-be-sintered green body (the to-be-sintered green body with a certain shape and density can facilitate operators to transport and place the to-be-sintered green body in the corresponding high-temperature and high-pressure equipment, reducing the difficulty of operation). By pressing the first mixture, a green body of a specific shape is obtained, which facilitates the direct application and storage of the new solid electrolyte material synthesized by the high-temperature and high-pressure reaction (the solid electrolyte in the all-solid-state metal ion battery is generally in the form of a thin sheet. After the to-be-sintered green body pressed into a thin sheet is subjected to a high-temperature and high-pressure reaction, a thin sheet-shaped solid electrolyte sheet that can be directly used can be obtained).
[0035] In combination with the second aspect, in a third possible implementation manner of the second aspect of the present application, the method for preparing the first mixed material in step 1 includes:
[0036] According to the chemical formula (Li 5-xa M x )Y(A 3-yb X y ) were weighed in a stoichiometric ratio and placed in a vacuum ball mill and ground at a speed of 350-450 rpm for 6-10 h.
[0037] In the above implementation process, the weighed raw materials are placed in a vacuum ball mill and ground at a speed of 350-450 rpm for 6-10 hours. The vacuum mill has good sealing and isolation properties, which can prevent the raw material powder from contacting the atmospheric environment and absorbing moisture in the atmospheric environment while making the various raw materials mixed evenly.
[0038] In addition, ball milling at a certain rotation speed in a vacuum tank can not only make the various raw material powders mixed more evenly, but also reduce the powder particle size and appropriately change the surface activity of the powder particles, so as to improve the reaction synthesis rate of the solid electrolyte material.
[0039] In combination with the second aspect, in a fourth possible implementation manner of the second aspect of the present application, the preset temperature is 300-1400° C., the preset pressure is 0.2-6 GPa, and the preset time is 5-90 min.
[0040] In the above implementation process, by appropriately increasing the pressure during the reaction synthesis of the sintered body, it is possible to induce lattice changes and promote the reaction synthesis efficiency of the high-solid electrolyte material. In addition, by appropriately increasing the sintering temperature and extending the holding time during the reaction synthesis of the sintered body, it is possible to improve the purity of the obtained solid electrolyte material.
[0041] In combination with the second aspect, in a fifth possible implementation of the second aspect of the present application, the crude solid electrolyte material includes (Li 5-x M x / a )Y(A 3-y X y / b ) and starting materials that do not participate in the reaction; the preparation method also includes a purification operation of the crude solid electrolyte material:
[0042] Grinding the crude solid electrolyte material to uniformly disperse the constituent materials to obtain a second mixed material;
[0043] sintering the second mixed material for a preset time at a preset temperature, a preset pressure and a moisture content of less than 0.01 ppm;
[0044] Among them, the preset temperature is not lower than 300°C, the preset pressure is not less than 0.2GPa, and the preset time is not less than 5 minutes.
[0045] In combination with the second aspect, in a sixth possible implementation of the second aspect of the present application, the preparation method of the second mixture includes: placing the crude solid electrolyte material in a vacuum ball mill and grinding it at a rotation speed of 350 to 450 rpm for 6 to 10 hours.
[0046] In the above implementation process, grinding the crude solid electrolyte material (which generally contains unreacted raw materials or other intermediates) can evenly mix the unreacted raw materials or incompletely reacted intermediates, breaking the original positional restrictions between the various powders to facilitate the transmission and diffusion reactions of the corresponding substances. The second mixed material is sintered for at least 5 minutes at a temperature of 300°C or above, a pressure of 0.2GPa or above, and a moisture content of less than 0.01ppm. High temperature and high pressure technology is then used again to encourage the unreacted or incompletely reacted intermediates to re-react, thereby obtaining a higher purity solid electrolyte material.
[0047] Grinding the solid electrolyte material using a vacuum ball mill can prevent the raw materials or other intermediate products in the solid electrolyte material that do not participate in the reaction from coming into contact with the atmosphere and absorbing moisture in the atmosphere, while ensuring that the various powders are mixed evenly.
[0048] In a third aspect, examples of the present application provide an all-solid-state lithium-ion battery comprising a solid-state electrolyte material.
[0049] In the above implementation process, the chemical formula provided by the first aspect is as follows (Li 5-x M x / a )Y(A 3-y X y / b ) is used to prepare a solid electrolyte (which can be a thin film or electrolyte sheet) for an all-solid-state lithium-ion battery, which can improve the electrical properties of the all-solid-state lithium-ion battery, such as ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art.
[0051] Figure 1 The XRD patterns of the products synthesized in Examples 1 to 4 and Comparative Examples 1 to 2 of the present application are shown;
[0052] Figure 2 This is a SEM image of the product synthesized in Example 1 of the present application;
[0053] Figure 3 This is a test chart of the ionic conductivity of the product synthesized in Example 4 of the present application. DETAILED DESCRIPTION
[0054] The embodiments of the present application will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, the conditions are carried out according to conventional conditions or manufacturer recommendations. The reagents or instruments used are not specified by the manufacturer and are conventional products that can be purchased commercially.
[0055] The following is a detailed description of a solid electrolyte material, a preparation method thereof, and an all-solid-state battery provided in the embodiments of the present application:
[0056] Metal-ion batteries, such as lithium-ion batteries, offer unparalleled advantages such as high energy density, high output voltage, long lifespan, and environmental friendliness, making them irreplaceable energy storage devices. Compared to organic liquid and gel electrolytes, solid-state electrolytes offer significant advantages in safety, thermal stability, and electrochemical stability.
[0057] The inventors believe that developing high-performance solid-state electrolyte materials is an important step in the development of all-solid-state metal batteries. Currently, reported solid-state electrolytes include NASICON-type electrolytes, LISICON-type electrolytes, perovskite-type solid electrolytes, antiperovskite-type solid electrolytes, garnet-type electrolytes, and sulfide electrolytes.
[0058] The inventors believe that existing solid-state electrolytes have low ionic conductivity and electrochemical stability, requiring further improvement. Furthermore, the inventors have discovered that most researchers have difficulty synthesizing high-purity solid-state electrolytes using traditional methods such as high-temperature solid-phase, sealed-tube, and melt processes.
[0059] Based on this, the inventors provide a method for preparing a solid electrolyte material, the chemical formula of which is (Li 5-x M x / a )Y(A 3-y X y / b ), the solid electrolyte material is a hexagonal crystal system; wherein M is a cation with a valence of a, and Y, A, and X are all anions. M includes one or more of H, Na, K, Rb, Mg, Ca, Sr, Ba, Zn, Al, Ga, Si, Ge, Sn, and P; Y is selected from at least one of O, S, and Se; A is selected from one of F, Cl, Br, and I; X has a valence of -b and is selected from at least one of F, Cl, Br, I, S, O, Se, N, OH, BF4, BH4, AlF4, and AlH4 that is different from A; 0≤x<5, 0≤y≤3. The preparation method of the solid electrolyte material comprises:
[0060] S1. Obtaining the body to be sintered
[0061] The body to be sintered includes the following chemical formula (Li 5-x M x / a )Y(A 3-y X y / b ) The mixture is mixed in the stoichiometric ratio shown; the water content of the sintered body is less than 0.01ppm.
[0062] For example, when a=b=1, the chemical formula is (Li 5-x M x )Y(A 3-y X y ), M is a +1 valent cation, X is a -1 valent anion, and 0≤x<5, 0≤y≤3.
[0063] For example, when x=0, the chemical formula becomes Li5Y(A 3-y X y ), and 0≤y≤3;
[0064] Illustratively, y includes, but is not limited to, a range between one or any two of 0, 0.5, 1, 2, and 3.
[0065] The present application does not limit the specific types and contents of the raw materials in the sintered body. Relevant personnel can make corresponding choices within the selection range of the above elements according to the type of all-solid-state metal ion battery to be prepared.
[0066] In one possible embodiment, Y is selected as O, A is selected as Br, and X is selected as Cl, so that a chemical formula such as Li5O(Br) suitable for all-solid-state lithium-ion batteries can be synthesized through subsequent high-temperature and high-pressure reactions. 3-y Cl y ) lithium-containing solid electrolyte materials.
[0067] When y=0, the stoichiometric ratio of Li2O:LiBr in the sintered body is 1:3, so that a lithium-containing solid electrolyte material with a chemical formula of Li5OBr3 suitable for all-solid-state lithium-ion batteries can be synthesized through a subsequent high-temperature and high-pressure reaction;
[0068] Among them, when y=0.5, the stoichiometric ratio of Li2O:LiBr:LiCl in the sintered body is 1:2.5:0.5, so that the chemical formula of Li5OBr suitable for all-solid-state lithium-ion batteries can be synthesized through subsequent high temperature and high pressure reactions. 2.5 Cl 0.5 Lithium-containing solid electrolyte materials;
[0069] When y=1, the stoichiometric ratio of Li2O:LiBr:LiCl in the sintered body is 1:2:1, so that a lithium-containing solid electrolyte material with a chemical formula of Li5OBr2Cl suitable for all-solid-state lithium batteries can be synthesized through a subsequent high-temperature and high-pressure reaction.
[0070] When y=2, the stoichiometric ratio of Li2O:LiBr:LiCl in the sintered body is 1:1:2, so that a lithium-containing solid electrolyte material with a chemical formula of Li5OBrCl2 suitable for all-solid-state lithium batteries can be synthesized through a subsequent high-temperature and high-pressure reaction.
[0071] Among them, when y=3, the stoichiometric ratio of Li2O:LiCl in the sintered body is 1:3, so that a lithium-containing solid electrolyte material with a chemical formula such as Li5OCl3 suitable for all-solid-state lithium-ion batteries can be synthesized through subsequent high-temperature and high-pressure reactions.
[0072] Alternatively, M is selected as Na (a=1), Y is selected as S, A is selected as Br, and X is selected as F (b=1). This facilitates the synthesis of a chemical formula suitable for all-solid-state lithium and / or sodium ion batteries through subsequent high temperature and high pressure reactions. 5-x Na x )S(Br 3-y F y ) of solid electrolyte materials, and has 0 <x<5,0≤y≤3。
[0073] Alternatively, M is selected as K (a=1), Y is selected as Se, A is selected as Cl, and X is selected as I (b=1). This facilitates the synthesis of a chemical formula suitable for all-solid-state lithium and / or potassium ion batteries through subsequent high-temperature and high-pressure reactions. 5-x K x )Se(Cl 3-y I y ) of solid electrolyte materials, and has 0 <x<5,0≤y≤3。
[0074] Alternatively, M is selected as Mg (a=2), Y is selected as S, A is selected as Br, and X is selected as Cl (b=1). This facilitates the synthesis of a chemical formula suitable for all-solid-state lithium and / or magnesium ion batteries through subsequent high-temperature and high-pressure reactions, such as (Li 5-x Mg x / 2 )S(Br 3-y Cl y ) of solid electrolyte materials, and has 0 <x<5,0≤y≤3。
[0075] Alternatively, M is selected as Al (a=3), Y is selected as O, A is selected as Br, and X is selected as S (b=2). This facilitates the synthesis of a chemical formula suitable for all-solid-state lithium and / or aluminum ion batteries through subsequent high temperature and high pressure reactions. 5-x Al x / 3 )O(Br 3-y S y / 2 ) of solid electrolyte materials, and has 0 <x<5,0≤y≤3。
[0076] The present application does not limit the preparation method of the sintered body. In one possible embodiment, the preparation method of the sintered body includes:
[0077] Step 1: Under the condition that the moisture content is less than 0.01 ppm, the raw materials are mixed according to a certain stoichiometric ratio to prepare a first mixed material.
[0078] The present application does not limit how to mix to prepare the first mixed material. In one possible implementation, all raw materials are placed together in a vacuum ball mill and ground at a rotation speed of 350-450 rpm for 6-10 hours.
[0079] Illustratively, the rotational speeds for ball milling Li2O, LiBr and LiCl in a vacuum ball mill include but are not limited to 350 rpm, 360 rpm, 375 rpm, 380 rpm and 450 rpm.
[0080] Exemplarily, the time for ball milling Li2O, LiBr and LiCl in a vacuum ball mill includes but is not limited to 6 h, 7 h, 7.5 h, 8.5 h and 10 h.
[0081] The present application does not limit the specific form of Li2O, LiBr and LiCl when preparing the first material mixture. For example, Li2O can be a block, LiBr can be a powder, and LiCl can be a powder. Accordingly, in order to facilitate the more uniform dispersion of the block Li2O with other powder raw materials when preparing the first material mixture, the block Li2O can be pre-ground before ball milling using a vacuum ball mill. In order to avoid the impact of contact with moisture in the atmospheric environment during the pre-grinding of raw materials and the weighing of each raw material on the synthesis of the solid electrolyte material, the pre-grinding of Li2O and the weighing of each powder can be carried out in a glove box.
[0082] In a possible embodiment, in order to prevent Li2O, LiBr and LiCl from contacting with moisture in the atmospheric environment during the mixing process, thereby affecting the chemical formula of Li5OBr 3-y Cl y For the synthesis of new solid electrolyte materials, operators can use a glove box to manually mix the powder.
[0083] Step 2: Press the first mixture under a pressure of 20-100 MPa for 1-5 minutes under the condition that the moisture content is less than 0.01 ppm.
[0084] Illustratively, the pressure for pressing the first mixed material includes, but is not limited to, one of 20 MPa, 40 MPa, 50 MPa, 85 MPa, and 100 MPa, or a range between any two of them.
[0085] Illustratively, the time for pressing the first mixed material includes, but is not limited to, one of 1 min, 1.5 min, 2 min, 4 min, and 5 min, or a range between any two of them.
[0086] This application does not limit how the first mixed material is pressed under conditions where the moisture content is less than 0.01 ppm. In one possible embodiment, the first mixed material is pressed in a glove box. Alternatively, the first mixed material is enclosed in an elastic isolation sleeve and the first mixed material in the elastic isolation sleeve is pressed using a liquid medium that can provide static pressure.
[0087] The present application does not limit the specific form of the body to be sintered. In one possible implementation, the first mixed material can be directly placed in a high-temperature and high-pressure synthesis reaction device for sintering.
[0088] S2. High temperature and high pressure sintering of the body to be sintered
[0089] The body to be sintered is placed under a preset temperature, preset pressure and moisture less than 0.01 ppm and sintered for a preset time; wherein the preset temperature is not lower than 300°C, the preset pressure is not less than 0.2 GPa, and the preset time is not less than 5 minutes.
[0090] Illustratively, the preset temperature includes but is not limited to one of 300° C., 500° C., 700° C., 900° C., and 1000° C., or a range between any two of the above.
[0091] Illustratively, the preset pressure includes but is not limited to one of 0.2 GPa, 1.5 GPa, 2 GPa, 4 GPa and 6 GPa, or a range between any two of them.
[0092] Exemplarily, the preset time includes but is not limited to one of 5 min, 30 min, 530 min, 70 min and 90 min, or a range between any two of them.
[0093] The present application does not limit the high-temperature and high-pressure reaction equipment used to sinter the body to be sintered. In one possible embodiment, a two-sided top press or a six-sided top large cavity press can be used to perform the sintering synthesis reaction.
[0094] The crude solid electrolyte material contains (Li 5-x M x / a )Y(A 3-y X y / b ), as well as raw materials that did not participate in the reaction or intermediate products that did not react completely. In order to improve the purity of the obtained solid electrolyte material, the example of this application also provides a purification operation of the crude solid electrolyte material:
[0095] Grinding the crude solid electrolyte material to uniformly disperse the components to obtain a second mixed material;
[0096] The second mixed material is sintered for a preset time at a preset temperature, a preset pressure, and a moisture content of less than 0.01 ppm, wherein the preset temperature is not less than 300° C., the preset pressure is not less than 0.2 GPa, and the preset time is not less than 5 minutes.
[0097] This application does not limit how the solid electrolyte material is used to obtain the second mixed material. In one possible embodiment, the second mixed material can be obtained by grinding the crude solid electrolyte material by manual grinding or mechanical grinding. To avoid exposure to moisture in the atmospheric environment during the grinding process, the crude solid electrolyte material can be manually or mechanically ground in a glove box.
[0098] Furthermore, the examples of the present application also provide a solid electrolyte material, which is obtained by the above-mentioned preparation method.
[0099] To facilitate subsequent purification, film formation, and tableting of the sintered solid electrolyte material to meet the requirements of all-solid-state metal ion batteries, the bulk solid electrolyte material obtained by the above preparation method can be ground to prepare solid electrolyte material powders of varying particle sizes. Prior to grinding the solid electrolyte bulk, the surface of the solid electrolyte bulk can be polished with sandpaper to remove impurities adhering to the bulk surface.
[0100] Furthermore, the examples of the present application also provide an all-solid-state lithium-ion battery, which is a lithium-containing solid electrolyte material prepared by the above-mentioned preparation method.
[0101] Optionally, relevant personnel can use the sodium- or potassium-containing solid electrolyte material prepared by the above preparation method to prepare an all-solid-state sodium ion or potassium ion battery with higher electrical performance.
[0102] The solid electrolyte material and preparation method of the present application are further described in detail below with reference to the examples.
[0103] Example 1
[0104] Example 1 of the present application provides a solid electrolyte material, which is prepared by the following method:
[0105] Li2O and LiBr in a molar ratio of 1:3 were weighed and placed in a vacuum ball mill (this process was carried out in a glove box) for thorough ball milling at a rotation speed of 400 rpm for 6 hours. The ball-milled powder was pre-pressed into a cylindrical shape at a pressure of 20-100 MPa and maintained at this pressure for 1-5 minutes (carried out in a glove box) to pre-press the raw materials into a complete cylindrical shape. The pre-pressed cylindrical blank was placed in a high-pressure synthesis block as a reactant. The assembled high-pressure synthesis block was placed in a synthesis chamber of a large-cavity press for reaction at a synthesis temperature of 600°C, a pressure of approximately 1 GPa, and a synthesis reaction time of approximately 60 minutes. After the reaction was completed, the temperature was lowered and the pressure was released, and the sample in the high-pressure synthesis block was quickly removed to obtain a reactant containing the target product Li5OBr3.
[0106] Example 2
[0107] Example 2 of the present application provides a solid electrolyte material, which differs from Example 1 in that in the preparation method of the solid electrolyte material provided in Example 2, the assembled high-pressure synthesis block is placed in the synthesis chamber of a large-cavity press for reaction, and the synthesis temperature is 800°C.
[0108] Example 3
[0109] Example 3 of the present application provides a solid electrolyte material, which differs from Example 1 in that in the preparation method of the solid electrolyte material provided in Example 3, the assembled high-pressure synthesis block is placed in the synthesis chamber of a large-cavity press for reaction, and the synthesis temperature is 1000°C.
[0110] Example 4
[0111] Example 4 of the present application provides a solid electrolyte material, which is different from Example 1 in that: in the preparation method of the solid electrolyte material provided in Example 4, the assembled high-pressure synthesis block is placed in the synthesis chamber of a large-cavity press for reaction, and the synthesis temperature is 800°C. After the reaction is completed, the temperature is lowered and the pressure is released, and the sample in the high-pressure synthesis block is quickly taken out to obtain the target product Li5OBr3 with lower purity. After it is taken out, it is placed in an agate mortar and manually ground for about 30 minutes, and then pressed into a complete cylindrical shape in a manual tablet press again, and the talc module is assembled. The assembled talc module is put back into the press for a high-temperature and high-pressure synthesis experiment, with a synthesis temperature of 800°C, a pressure of about 1GPa, and a synthesis reaction time of about 30 minutes. After the reaction is completed, the temperature is lowered and the pressure is released, and the sample in the high-pressure synthesis block is quickly taken out to obtain the target product Li5OBr3 with higher purity.
[0112] Comparative Example 1
[0113] The difference between Comparative Example 1 and Example 1 is that in the preparation process of Comparative Example 1, the corresponding raw materials are weighed according to the molar ratio of Li2O:LiBr being 1:4.
[0114] Comparative Example 2
[0115] The difference between Comparative Example 2 and Example 1 is that: in the preparation process of Comparative Example 2, the raw materials were weighed according to the molar ratio of Li2O:LiBr of 1:3 under atmospheric environment, and the weighed raw materials were placed in a non-vacuum ball mill and fully ball milled; and the ball-milled powder was pre-pressed into a cylindrical shape under atmospheric environment.
[0116] Experimental example
[0117] (1) X-ray diffraction tests were performed on the reaction products provided in Examples 1 to 4 and Comparative Examples 1 to 2. The results are as follows: Figure 1 shown.
[0118] Result analysis: From Figure 1 It can be seen that the solid electrolyte material provided in Examples 1 to 4 of the present application is a chemical formula of (Li 5-x M x / a )Y(A 3-y X y / b As the temperature increases, the purity of the prepared new solid electrolyte material becomes higher.
[0119] By comparing Example 1 and Comparative Example 1, it can be seen that arbitrarily adjusting the molar ratio of Li2O:LiBr to 1:4 results in a mixture containing Li2O, LiBr and Li5OBr3, and a material with the chemical formula Li6OBr4 cannot be obtained.
[0120] Comparing Example 1 and Comparative Example 2, it can be seen that in an atmospheric environment (moisture content greater than 0.01 ppm), the sample raw material will absorb water and contain a large amount of impurity peaks, making it impossible to synthesize a relatively pure target product Li5OBr3.
[0121] (2) The morphology of the reaction product provided in Example 1 was observed by scanning electron microscopy. The results are as follows: Figure 2 shown.
[0122] Result analysis: It can be seen from the figure that the particles are evenly distributed and the interface is relatively smooth.
[0123] (3) The solid electrolyte material provided in Example 3 of the present application was tested for ionic conductivity, and the results are as follows: Figure 3 shown.
[0124] Result analysis: The ionic conductivity of the solid electrolyte material provided in Example 4 of the present application at 25°C is 0.57×10- 8 S / cm, the ionic conductivity of the solid electrolyte material provided in Example 4 of the present application at 120°C is 0.28×10 -5 S / cm.
[0125] The above description is merely a preferred embodiment of the present application and is not intended to limit the present application. Various modifications and variations are possible for those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present application shall be included within the scope of protection of the present application.
Claims
1. A method for preparing a solid electrolyte material, characterized in that: The preparation method comprises: A sintered body is obtained, wherein the sintered body comprises The raw materials are mixed in a stoichiometric ratio, and the water content of the sintered body is less than 0.01 ppm; sintering the body to be sintered for a preset time at a preset temperature, a preset pressure and a moisture content of less than 0.01 ppm; The preset temperature is not less than 300°C, the preset pressure is not less than 0.2 GPa, and the preset time is not less than 5 min. The chemical formula of the solid electrolyte material is , belongs to the hexagonal crystal system; among them, M is a cation with a valence of a, Y 、 A and X are all anions; M Including one or more of H, Na, K, Rb, Mg, Ca, Sr, Ba, Zn, Al, Ga, Si, Ge, Sn, and P; Y At least one selected from O, S, Se; A One selected from F, Cl, Br, I; X The valence state is -b, and the valence state is selected from F, Cl, Br, I, S, O, Se, N, OH, BF4, BH4, AlF4, AlH4, which is different from the above A At least one of; 0≤x<5, 0≤y≤3; The crude solid electrolyte material includes the Solid electrolyte material and starting materials; the preparation method also includes a purification operation of the crude solid electrolyte material: Grinding the crude solid electrolyte material to uniformly disperse the solid electrolyte material and the starting materials to obtain a second mixed material; sintering the second mixed material for a preset time at a preset temperature, a preset pressure and a moisture content of less than 0.01 ppm; Wherein, the preset temperature is not less than 300°C, the preset pressure is not less than 0.2 GPa, and the preset time is not less than 5 minutes.
2. The preparation method according to claim 1, characterized in that The chemical formula of the solid electrolyte material is Li5 YA 3.
3. The preparation method according to claim 2, characterized in that The chemical formula of the solid electrolyte material is Li5O A 3.
4. The preparation method according to claim 2, characterized in that The chemical formula of the solid electrolyte material is Li5OBr3.
5. The preparation method according to claim 1, characterized in that The chemical formula of the solid electrolyte material is Li 5- x Mg x / 2 O A 3, of which 0 <x<5。 6. The preparation method according to claim 1, characterized in that The chemical formula of the solid electrolyte material is Li5SBr 3-y Cl y , where 0≤y≤3.
7. The preparation method according to claim 1, characterized in that The chemical formula of the solid electrolyte material is Li5OBr 3-y S y / 2 , where 0 <y≤3。 8. The preparation method according to claim 1, characterized in that The body to be sintered includes Li2Y, LiA and LiX mixed in a stoichiometric ratio.
9. The preparation method according to claim 8, characterized in that The body to be sintered includes Li2O, LiA and LiX mixed in a stoichiometric ratio of 1:(3-y):y, where 0≤y≤3.
10. The preparation method according to claim 8, characterized in that The body to be sintered includes Li2O, LiBr and LiCl mixed in a stoichiometric ratio of 1:(3-y):y, where 0≤y≤3.
11. The preparation method according to claim 8, characterized in that The body to be sintered includes Li2O and LiBr mixed in a stoichiometric ratio of 1:
3.
12. The preparation method according to claim 1, characterized in that The method for preparing the body to be sintered comprises: Step 1: Under the condition that the moisture content is less than 0.01ppm, the raw materials are mixed according to the chemical formula The first mixture is prepared by mixing the mixture in a metering ratio of Step 2: Press the first mixture under a pressure of 20-100 MPa for 1-5 minutes under the condition that the moisture content is less than 0.01 ppm.
13. The preparation method according to claim 12, characterized in that The method for preparing the first mixed material in step 1 comprises: According to the chemical formula The raw materials required in the stoichiometric ratio are placed in a vacuum ball mill and ground at a speed of 350-450 rpm for 6-10 hours.
14. The preparation method according to claim 1, characterized in that The preset temperature is 300-1400° C., the preset pressure is 0.2-6 GPa, and the preset time is 5-90 min.
15. The preparation method according to claim 1, characterized in that The preparation method of the second mixed material comprises: The crude solid electrolyte material is placed in a vacuum ball mill and ground at a speed of 350-450 rpm for 6-10 hours.
16. An all-solid-state lithium-ion battery, characterized in that: The solid electrolyte material is prepared according to the preparation method of claim 2.
Citation Information
Patent Citations
Solid electrolyte material, preparation method thereof, solid electrolyte sheet and all-solid-state battery
CN113299979A
Preparation method of sulfide solid electrolyte
CN114421003A